HbA1c test awareness, sociodemographic characteristics and lifestyle behaviour among type 2 diabetes mellitus patients - George, Nenmanikkara Geoviya; Kamath, Manjeshwar Sahana; C. K., Megha; Kolar, Reshma (International Journal of Research in Medical Sciences, 2025)
Background: Glycated hemoglobin (HbA1c) is a key biomarker for long-term glycemic control. The studies have shown that patients having an understanding of HbA1c values in diabetic patients is associated with better glycemic control and self-care practices. This study aims to assess HbA1c test awareness among type 2 diabetes mellitus (T2DM) patients and examine its association with sociodemographic and lifestyle factors. Methods: This cross-sectional study was conducted among 230 type 2 diabetes mellitus patients using purposive sampling and the participants were recruited from outpatient and laboratory department of a hospital in Mangaluru, Karnataka, India. Awareness of HbA1c test was assessed using a structured questionnaire and analyzed in relation to demographic and lifestyle variables. Chi-square test were used for the analysis of data using statistical package for the social sciences (SPSS) software, and p<0.05 was considered statistically significant. Results: Out of 230 participants, 56.5% were male and 43.5% were aged 50–69 years. Only a minority of participants (16.1%) were aware of the HbA1c test. The HbA1c test awareness was not significantly associated with age, gender, education, employment, income, smoking, alcohol use, medication adherence, or diet adherence. Conclusions: Awareness of HbA1c test among T2DM patients was limited. Structured patient education and counseling programs focusing on HbA1c monitoring may empower patients to achieve better glycemic control and reduce the risk of diabetes-related complications.